Minor fruits for more income - Lata, Kanak; Kumar, Raj; Jadav, J K (Indian Horticulture, 2019)
The KVK, Godhra, has conducted various training programmes for farm women/home makers in areas of nutrition and preservation. Since Panchmahal district has substantial area under underutilized horticultural fruit crops. There is immense scope to generate additional income for women which can be facilitated through skill training. The technique of preservation of seasonal minor fruits such as tamarind, karonda, khirni, fig, wood apple, mulberry and phalsa in form of squash, syrup, jam, jelly ready to serve beverages, chutney, pickle, dehydrated products by using standardized techniques have been effectively demonstrated and popularized.